Meta‐Analyses Support Previous and Novel Autism Candidate Genes: Outcomes of an Unexplored Brazilian Cohort. Issue 2 (6th November 2019) - da Silva Montenegro, Eduarda Morgana; Costa, Claudia Samogy; Campos, Gabriele; Scliar, Marília; de Almeida, Tatiana Ferreira; Zachi, Elaine Cristina; Silva, Isabela Maya Wahys; Chan, Ada J. S.; Zarrei, Mehdi; Lourenço, Naila C. V.; Yamamoto, Guilherme Lopes; Scherer, Stephen; et al.
Abstract : Large genomic databases of neurodevelopmental disorders (NDD) are helpful resources of genomic variations in complex and heterogeneous conditions, as Autism Spectrum Disorder (ASD). We evaluated the role of rare copy number variations (CNVs) and exonic de novo variants, in a molecularly unexplored Brazilian cohort of 30 ASD trios (n = 90), by performing a meta‐analysis of our findings in more than 20, 000 patients from NDD cohorts. We identified three pathogenic CNVs: two duplications on 1q21 and 17p13, and one deletion on 4q35. CNVs meta‐analysis ( n = 8, 688 cases and n = 3, 591 controls) confirmed 1q21 relevance by identifying duplications in other 16 ASD patients. Exome analysis led the identification of seven de novo variants in ASD genes (SFARI list): three loss‐of‐function pathogenic variants in CUL3, CACNA1H, and SHANK3 ; one missense pathogenic variant in KCNB1 ; and three deleterious missense variants in ATP10A, ANKS1B, and DOCK1 . From the remaining 12 de novo variants in non‐previous ASD genes, we prioritized PRPF8 and RBM14 . Meta‐analysis ( n = 13, 754 probands; n = 2, 299 controls) identified six and two additional patients with validated de novo variants in PRPF8 and RBM14, respectively. By comparing the de novo variants with a previously established mutational rate model, PRPF8 showed nominal significance before multiple test correction ( P = 0.039, P ‐value adjusted = 0.079, binomial test), suggesting its relevance to ASD. Approximately 60% of our patients presented comorbidities, and the diagnostic yield was estimated in 23% (7/30: three pathogenic CNVs and four pathogenic de novo variants). Our uncharacterized Brazilian cohort with tetra‐hybrid ethnic composition was a valuable resource to validate and identify possible novel candidate loci. Autism Res 2020, 13: 199–206 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: We believed that to study an unexplored autistic population, such as the Brazilian, could help to find novel genes for autism. In order to test this idea, with our limited budget, we compared candidate genes obtained from genomic analyses of 30 children and their parents, with those of more than 20, 000 individuals from international studies. Happily, we identified a genetic cause in 23% of our patients and suggest a possible novel candidate gene for autism ( PRPF8 ).